Environmental benefit-detriment thresholds for flow battery energy storage systems: A case study in California. (15th October 2021) - Tian, Shan; He, Haoyang; Kendall, Alissa; Davis, Steven J.; Ogunseitan, Oladele A.; Schoenung, Julie M.; Samuelsen, Scott; Tarroja, Brian
Highlights: Combines life cycle analysis and electric grid dispatch modeling methods. Compares emissions reduced from battery use with emissions from battery production. Calculates net emissions reductions of flow batteries at increasing grid capacities. Capacity thresholds exist where emissions reduction benefits are maximized. Deploying too much flow battery capacity can reduce or negate emissions reductions. Abstract: Energy storage systems are critical for enabling the environmental benefits associated with capturing renewable energy to displace fossil fuel-based generation, yet producing these systems also contributes to environmental impacts through their materials use and manufacturing. As energy storage capacity is scaled up to support increasingly renewable grids, the environmental benefits from their use may scale at different rates than the environmental impacts from their production. This implies the existence of capacity thresholds beyond which installing additional storage capacity may be environmentally detrimental. Identifying such thresholds are important for ensuring that energy storage capacity selection in future grids are consistent with net emissions reduction goals, but such thresholds have not been studied in the present literature. To identify such thresholds, here we combine electric grid dispatch modeling with life cycle analysis to compare how the emissions reductions from deploying three different flow battery energy storage types on a future California grid (>80% wind and solar) compare with emissions contributions from producing such batteries as total battery capacity installed on the grid increases. Depending on the type of battery and environmental impact indicator (greenhouse gas or particulate matter emissions), we find that the marginal environmental benefits of storage begin to diminish at deployed capacities of 38–76% of the mean daily renewable generation (256–512 GWh in our California scenarios) and reach zero at 105–284% of mean daily renewable generation (700–1810 GWh). Such storage capacities are conceivable, but upstream impacts of storage must be assessed in evaluating the environmental benefits of large-scale storage deployment, or they could negate the environmental benefits of regional electricity system decarbonization.